The Racovitzan impediment and the hidden biodiversity of unexplored environments. Issue 1 (5th September 2018) - Ficetola, Gentile Francesco; Canedoli, Claudia; Stoch, Fabio
Abstract : Article impact statement : Biodiversity of unexplored and unmapped environments cannot be conserved until they have been described, mapped, and analyzed.